(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
Background: Distal extension edentulism can affect the patients ability to function as a dentate person. A well-made removable partial denture that has appropriate extensions, borders and ridge-to-dentition relationship will benefit the partially edentulous patient by providing increased comfort and improved dental function. This article described a patient who had a bilateral distal extension removable partial denture in both upper and lower arch. The prosthesis showed a successful rehabilitation with proper function and aesthetics. Methods: A Kennedy class I bilateral free end saddle edentulous arch in both upper and lower arch was rehabilitated with removable cast partial denture. The case had the reasonable amount of crown: root ratio for the remaining abutment teeth for placement of metal framework, occlusal rest and cast clasp. Results: The delivered denture showed proper sitting of occlusal rest and cast clasp. Retention and stability was acceptable. Occlusion had achieved its desired occlusion scheme. Conclusion: Removable cast partial denture is a suitable option for the rehabilitation of partially edentulous case if the case has such amount of abutment teeth remaining with healthy periodontal condition. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16616 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 60